Revenue and Quality of Earnings by Listed Companies in the Property and Construction Industry Group - Sritarapipat, Onruedee (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
The objectives of this research were 1) to study trends of revenue from operations, accounting profit, and net cash flows from operating activities, and also the quality of earnings measured by operating cash index, 2) to study the relationship between revenue from operations and quality of earnings, and 3) to compare the quality of earnings among the industry group and business size. A total of 53 samples in this study were 41 property companies and12 construction companies. The data were collected from annual financial statements during the years 2007 to 2012. This study classified the property and construction Industry group into large, medium and small groups based on their fixed assets. Descriptive and trend statistical analysis methods were used in this research. Hypotheses were tested by correlation coefficients, t-test, and One-way ANOVA with a statistical significance at .05 level. The results indicated that from 2007 to 2012, 1) most listed companies in the property Industry group had non-smoothers in revenue from operations, accounting profit, net cash flows from operating activities, and an operating cash index, which indicated that most listed companies had non-smoothers in operating efficiency, and non-smoothers in profitability. In 2012 the results indicated that most listed companies had an operating cash index higher than 1, which indicated that most listed companies had net cash flows from operating activities higher than accounting profit, and showed the quality of earnings and accounting profit that could be allocated for cash. 2) Most listed companies in the construction Industry group had non-smoothers in revenue from operations, accounting profit, and the operating cash index, which indicated that most listed companies had non- smoothers in operating efficiency to make revenue from an operation and non-smoothers in profitability, but had an increase in net cash flows from operating activities. In 2012 the results indicated that most listed companies had an operating cash index higher than 1, which indicated that most listed companies had net cash flows from operating activities higher than accounting profits, and showed the quality of earnings and accounting profit that could be allocated for cash. Furthermore, 3) the result showed that the relation between revenue from operations and quality of earnings of listed companies in the property Industry group were positive, which indicated that the quality of earnings depended on revenue from operations, but listed companies in the construction Industry group did not show a relationship. Additionally, 4) the result showed that the quality of earnings were not significantly different in accordance with the industry group and the business size.